2020
DOI: 10.1002/adfm.202000841
|View full text |Cite
|
Sign up to set email alerts
|

2D Titanium Carbide (Ti3C2Tx) in Accommodating Intraocular Lens Design

Abstract: While intraocular lenses (IOL) are used to restore visual acuity in cataract patients, they are limited in their development as no clinically available lens can effectively mimic the accommodative function of the eye's natural lens. The optoelectronic properties of 2D transition metal carbides and/or nitrides (MXenes), including high electronic conductivity, optical transparency, flexibility, biocompatibility, and hydrophilicity, suggest potential use within an accommodating IOL. This study investigates the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…[ 46 ] Although previous studies have shown that MXene nanosheets have good biocompatibility, the research on blood compatibility is still obscure yet. [ 47 ] In this research, we investigated the compatibility of Ti 3 C 2 T x MXene nanosheets in human blood (Figure 5b). Tables S1 and S2 (Supporting Information) show the details of different blood parameters before and after adding MXene/AC absorbents with the same mass loading in 12 blood samples (6 for MXene while 6 for AC).…”
Section: Resultsmentioning
confidence: 99%
“…[ 46 ] Although previous studies have shown that MXene nanosheets have good biocompatibility, the research on blood compatibility is still obscure yet. [ 47 ] In this research, we investigated the compatibility of Ti 3 C 2 T x MXene nanosheets in human blood (Figure 5b). Tables S1 and S2 (Supporting Information) show the details of different blood parameters before and after adding MXene/AC absorbents with the same mass loading in 12 blood samples (6 for MXene while 6 for AC).…”
Section: Resultsmentioning
confidence: 99%
“…Conductive inks formulated with binders have tuneable electrical properties depending on the proportion of conductive fillers used. Some articles report conductivity as a function of filler loading [22,31,55,[84][85][86][87][88][89][90][91][92] , and the most conductive formulations are shown for these cases. Sheet based coatings show the highest electrical conductivities, reaching 10 6 S m -1 , with the closest textile displaying two orders of magnitude lower values [93] than the best performing sheet [94] in terms of bulk conductivity.…”
Section: Electrical Propertiesmentioning
confidence: 99%
“…Textile (Spandex) 1.00E+01 [176] Textile (TPU) 1.00E+00 [177] Graphene + MXene Sheet (Polyester) 1.20E+05 [178] MXene Sheet (Acrylate) 2.99E+02 5.77E+04 [91] Sheet (Filter Paper) 2.76E+03 [179] Sheet (PET) 5.21E+00 4.50E+05 [23,72,94] Sheet (PET) CNTs 6.15E+00 1.05E+06 [55] Sheet (PTFE) 1.00E+03 [180] Sheet (Paper) 1.67e+01 to 2.23e+03…”
Section: Graphenementioning
confidence: 99%
“…Additionally, owing to the high electronic conductivity, optical transparency, flexibility, biocompatibility, and hydrophilicity, it has been shown that Ti 3 C 2 T x thin films can be used as optically transparent electrodes for accommodative intraocular lenses (IOLs). [111] In using MXenes as IOLs, these thin film coatings maintain the image quality of the lenses, [109] Copyright 2019, Wiley-VCH. b) Photoresponse of Ti 3 C 2 T x thin film (38 nm thick) with and without UV irradiation and exposure to ambient air for 30 min.…”
Section: Optical Detectionmentioning
confidence: 99%